Potassium‐Promoted Molybdenum Carbide as a Highly Active and Selective Catalyst for CO2 Conversion to CO. Issue 11 (10th May 2017) - Porosoff, Marc D.; Baldwin, Jeffrey W.; Peng, Xi; Mpourmpakis, Giannis; Willauer, Heather D.
Abstract: The high concentration of CO2 bound in seawater represents a significant opportunity to extract and use this CO2 as a C1 feedstock for synthetic fuels. Using an existing process, CO2 and H2 can be concurrently extracted from seawater and then catalytically reacted to produce synthetic fuel. Hydrogenating CO2 directly into liquid hydrocarbons is exceptionally difficult, but by first identifying a catalyst for selective CO production through the reverse water–gas shift (RWGS) reaction, CO can then be hydrogenated to fuel through Fischer–Tropsch (FT) synthesis. Results of this study demonstrate that potassium‐promoted molybdenum carbide supported on γ‐Al2 O3 (K‐Mo2 C/γ‐Al2 O3 ) is a low‐cost, stable, and highly selective catalyst for RWGS over a wide range of conversions. These findings are supported by X‐ray diffraction, scanning electron microscopy with energy‐dispersive X‐ray spectroscopy, X‐ray photoelectron spectroscopy, and density functional theory calculations. Abstract : Potassium can stabilize : Modifying a molybdenum carbide catalyst supported on γ‐alumina with potassium improves selectivity towards CO and catalyst stability during the reverse water–gas shift reaction. Over a broad conversion range, the selectivity to CO is maintained near 95 %.